Pengaruh Agresivitas Pajak Pada Corporate Social Responsibility dengan Ukuran Perusahaan Sebagai Pemoderasi - Suryadewi, Ida Ayu Intan; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 23 No 1 (2018), 2018)
Corporate Social Responsibility (CSR) is a business commitment to contribute to sustainable economic development that is implemented by establishing a partnership with employees, corporate representatives and the general public. A company's CSR can be affected by tax aggressiveness and firm size. The purpose of this study is to determine the effect of tax aggressiveness on corporate social responsibility and to determine whether firm size can moderate the effect of tax aggressiveness on corporate social responsibility. This research was conducted on mining companies listed on the Stock Exchange Indoneisa (BEI) in 2014-2016. The sampling method was purposive sampling. Data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of research, it is known that tax aggressiveness negatively affect corporate social responsibility. This research also shows that firm size is able to moderate the influence of tax aggressiveness on corporate social responsibility. Keywords : Corporate Social Responsibility, Tax Aggressiveness, Firm Size